A comparison of susceptibility to stocks of Trypanosoma vivax of Glossina pallidipes from allopatric populations in Kenya - Moloo, S.K.; Okumu, I.O. (Wiley, 1995)
This paper compares the susceptibility of Glossina pallidipes to stocks of Trypanosoma vivax. The first comparison on infection rates in male and female Glossina pallidipes which originated from Nguruman or Shimba Hills, Kenya, by Trypanosoma vivax stocks isolated in Galama, kenya, or Zaria, Nigeria. The second comparison is the same as the first except it is on both sexes.